|-5/14|-3/7:6/11
thu gọn các biểu thức sau
a)C=3^14+3^15+3^16+3^17+...+3^n
b)D=3^11+3^14+3^17+3^20+...+3^2021
c) E= -5^2-5^4-5^6-5^8-...-5^1000
d)F=-5^21-5^23-5^25-5^27-...-5^2019
e)M=7^2-7^4+7^6-7^8+...-7^1000
d)N=-12+11^2+11^3-11^4-11^5+...+11^498+11^499
b: \(27D=3^{14}+3^{17}+...+3^{2024}\)
\(\Leftrightarrow26D=3^{2024}-3^{11}\)
hay \(D=\dfrac{3^{2024}-3^{11}}{26}\)
c: \(25E=-5^4-5^6-...-5^{1002}\)
\(\Leftrightarrow24E=-5^{1002}+5^2\)
hay \(E=\dfrac{-5^{1002}+5^2}{24}\)
thực hiện phép tính
E = (12/35-6/ 7+18/14):6/-7-(-2/5)-1
G=(-5/7-7/9+9/11-11/13)(12/4-3/4)/ (10/21+14/27-6/11+22/39):(6/3-2/3)
1/2+2/3+3/4+4/5+5/6+6/7+7/8+8/9+9/10+10/11+11/12+12/13+13/14+14/15=?
d=43/37×23/15-43/37×8/15+31/37
E= -5/24×9/11- 5/24×2/11+7/12
a) 3/7– -11/14- 7/3×6/7
b) 6/5:3/2+ -2/3×9/14
d=43/37d=43/37 × 23/15−43/3723/15−43/37 × 8/15+31/378/15+31/37
=43/37=43/37 x 23/15+43/3723/15+43/37 x (−8/15)+31/37(−8/15)+31/37
=43/37(23/15−8/15)+31/37=43/37(23/15−8/15)+31/37
=43/37.1+31/37=43/37.1+31/37
=2=2
E=−5/24E=−5/24 × 9/11−5/249/11−5/24 × 2/11+7/122/11+7/12
=−5/24(9/11+2/11)+7/12=−5/24(9/11+2/11)+7/12
=−5/24.1+7/12=−5/24.1+7/12
=3/8=3/8
a)3/7–−11/14−7/3×6/7a)3/7–−11/14−7/3×6/7
=3/7−−11/14−2=3/7−−11/14−2
=3/7+11/14−2=3/7+11/14−2
=−11/14=−11/14
b)6/5:3/2+−2/3×9/14b)6/5:3/2+−2/3×9/14
=4/5−3/7=4/5−3/7
=13/35
d=43/37d=43/37 × 23/15−43/3723/15−43/37 × 8/15+31/378/15+31/37
=43/37=43/37 x 23/15+43/3723/15+43/37 x (−8/15)+31/37(−8/15)+31/37
=43/37(23/15−8/15)+31/37=43/37(23/15−8/15)+31/37
=43/37.1+31/37=43/37.1+31/37
=2=2
E=−5/24E=−5/24 × 9/11−5/249/11−5/24 × 2/11+7/122/11+7/12
=−5/24(9/11+2/11)+7/12=−5/24(9/11+2/11)+7/12
=−5/24.1+7/12=−5/24.1+7/12
=3/8=3/8
a)3/7–−11/14−7/3×6/7a)3/7–−11/14−7/3×6/7
=3/7−−11/14−2=3/7−−11/14−2
=3/7+11/14−2=3/7+11/14−2
=−11/14=−11/14
b)6/5:3/2+−2/3×9/14b)6/5:3/2+−2/3×9/14
=4/5−3/7=4/5−3/7
=13/35
5/7 + 3/14 = ?
11/12 - 5/6 = ?
6 x 5/18 = ?
4/5 : 3/7 = ?
5/7 + 3/14 = 13/14
11/12 - 5/6 = 1/12
6 x 5/18 = 5/3
4/5 : 3/7 = 28/15
5/7 + 3/14 = 17/14
11/12 - 5/6 = 1/12
6 x 5/18 = 5/3
4/5 : 3/7 = 28/15
\(\dfrac{5}{7}+\dfrac{3}{14}=\dfrac{10}{14}+\dfrac{3}{14}=\dfrac{13}{14}\)
\(\dfrac{11}{12}-\dfrac{5}{6}=\dfrac{11}{12}-\dfrac{10}{12}=\dfrac{1}{12}\)
\(6\times\dfrac{5}{18}=15\)
\(\dfrac{4}{5}:\dfrac{3}{7}=\dfrac{28}{15}\)
a) 5/9*10/11+5/9*14/11-5/9*15/11 b) 6/7*8/13+6/13*9/7-3/13*6/7 Giúp mk vs ạ
a, \(\dfrac{5}{9}.\dfrac{10}{11}+\dfrac{5}{9}.\dfrac{14}{11}-\dfrac{5}{9}.\dfrac{15}{11}=\dfrac{5}{9}.\left(\dfrac{10}{11}+\dfrac{14}{11}-\dfrac{15}{11}\right)=\dfrac{5}{9}.\dfrac{9}{11}=\dfrac{5}{11}\)
b, \(\dfrac{6}{7}.\dfrac{8}{13}+\dfrac{6}{13}.\dfrac{9}{7}-\dfrac{3}{13}.\dfrac{6}{7}\)\(=\dfrac{6}{7}.\left(\dfrac{8}{13}-\dfrac{3}{13}\right)+\dfrac{6}{13}.\dfrac{9}{7}=\dfrac{6}{7}.\dfrac{5}{13}+\dfrac{54}{91}=\dfrac{30}{91}+\dfrac{54}{91}=\dfrac{84}{91}=\dfrac{12}{13}\)
Bạn ơi, gõ latex cho dễ nhìn nhé!
a: =35/17-18/17-9/5+4/5
=1-1=0
b: =-7/19(3/17+8/11-1)
=7/19*18/187=126/3553
c: =26/15-11/15-17/3-6/13
=1-6/13-17/3
=7/13-17/3=-200/39
bài 1 tính
a) (3/7+-9/8)+(5/8+-6/14)
b) (-5/7+3/11)+(-11/14+14/-11)
c)(-4/5+2/3)+(-5/4+19/5)+(7/3.2)
d)9/16.13/4-9/4.5/16+9/16.17/4
(-5) + (-7) + (-8) + (-3) =
(-4)+((-2)+(-5)+(-6)=
(-8)+(-11)+(-4)+(-2)=
(-9)+((-15)+(-6)+(-3)=
(-12)+(-9)+(-3)+(-8)=
(+3)+(+11)+(+14)+(+7)=
(+9)+(+5)+(+14)+(+2)=
(+12)+(+10)+(+3)+(+5)=
(+4)+(+7)+(+12)+(+15)=
(+20)+(+14)+(+3)+(+7)=
ai lam minh tick cho
a: =-5-7-8-3=-26
b: =-4-2-5-6=-17
c: =-8-11-4-2=-25
d: -9-15-6-3=-30
e: =-12-9-3-8=-32
gúp mik với
a 8/15+3/15:1/5
b 3/14-2/3+11/14
c 7/15*5/3+7/15*2/3
d 6/11-3/5+5/11
a) 8/15 + 1 = 23/15
b) 3/14 + 11/14 - 2/3 = 1- 2/3 = 1/3
c) 7/15 * (5/3+2/3) = 7/15 * 7/3= 49/45
d) 6/11 + 5/11 - 3/5 = 1 - 3/5 = 2/5